Islamic Philosophy as the Foundation of Modern Education: A Systematic Review - Tri Muryanti; Sulastri Sulastri; Dian Lestari; Mike Atnelie; Lelaini Lelaini (Journal of Social Work and Science Education, 2026)
Modern education is often dominated by pragmatic and secular approaches that emphasize technological progress and efficiency, while tending to neglect spiritual and ethical dimensions. Islamic philosophy, with its holistic view of humankind, knowledge, and the purpose of life, offers a normative and epistemological foundation that can integrate intellectual, moral, and spiritual aspects into contemporary education. This study conducted a Systematic Literature Review (SLR) to identify and analyze key themes in the discourse of educational philosophy in Indonesia. This study searched international and national indexed databases such as Scopus, Google Scholar, ERIC, and DOAJ, and selected 15 scientific articles published between 2020 and 2024. Using the PRISMA 2020 protocol, the analysis shows that Islamic philosophy makes a significant contribution to modern education through three aspects: (1) the integration of revelation and reason as the epistemological basis of education; (2) the formation of character and morals as a pedagogical orientation; and (3) the balance between worldly and hereafter knowledge in the curriculum. These findings affirm the role of Islamic philosophy as a foundation for modern education, capable of bridging knowledge and values, and shaping intelligent, moral, and civilized individuals. Further empirical research is needed to evaluate the implementation of these principles in curricula and educational practices in the digital age.